Is TNF inhibitor exposure a risk factor for amyotrophic lateral sclerosis?. (29th May 2019) - Petitpain, Nadine; Devos, David; Bagheri, Haleh; Rocher, Fanny; Gouraud, Aurore; Masmoudi, Kamel; Coquerel, Antoine
Abstract: TNFα modulation has been reported to be either beneficial or detrimental in amyotrophic lateral sclerosis (ALS) and therefore appears as a key issue. We analysed the relationship between TNFα inhibitor (TNFi) exposure and ALS. We performed descriptive analysis of ALS reports in patients treated with TNFi, registered in the French Pharmacovigilance Database (FPvD) and disproportionality analyses by the 'case'/'non‐case' method in FPvD and worldwide database (Vigibase ® ). The 8 retrieved ALS cases from the FPvD were 5 with limb‐onset and 3 with bulbar‐onset forms, in patients aged 43–75 years old, mainly treated for inflammatory rheumatism. The time to onset of the first symptoms ranged from 12 to 108 months, and the cumulative TNFi exposure before the diagnosis ranged from 12 to 120 months. TNFi was discontinued and thereafter survival ranged between 12 and 20 months. Disproportionality analyses showed significant associations between TNFi exposure and ALS in the FPvD and Vigibase ® (160 ALS cases), regardless comparators. A putative association between TNFi and ALS must be interpreted cautiously, but TNFi could act as a predisposing or risk factor. TNFi should therefore be avoided in patients with a known risk of ALS and discontinued in the case of neurological signs of ALS.